2000
DOI: 10.1093/rheumatology/39.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Development of a disease activity index for the assessment of reactive arthritis (DAREA)

Abstract: DAREA constitutes a reliable score which can easily be assessed on a day-to-day office work basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 19 publications
0
44
0
9
Order By: Relevance
“…Although other composite disease activity measures have been proposed for use in PsA, including composite measures developed for RA (18) and reactive arthritis (19), none included evaluation of joints, skin, enthesitis, and patient-reported outcomes. When considering criteria that can be used as a target for treatment, it is imperative that all aspects of disease are considered to ensure that patients are not undertreated.…”
Section: Discussionmentioning
confidence: 99%
“…Although other composite disease activity measures have been proposed for use in PsA, including composite measures developed for RA (18) and reactive arthritis (19), none included evaluation of joints, skin, enthesitis, and patient-reported outcomes. When considering criteria that can be used as a target for treatment, it is imperative that all aspects of disease are considered to ensure that patients are not undertreated.…”
Section: Discussionmentioning
confidence: 99%
“…These indices are based on a recently developed simple disease activity index for reactive arthritis (DAREA), which consists of an arithmetical sum of five core set variables [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies showed SDAI as a valid and sensitive assessment of disease activity and treatment response, when compared with DAS28-ESR and ACR response criteria [7][8][9]. SDAI is easy to calculate and is a viable tool for day-to-day clinical assessments of RA treatment [12]. Aletaha et al [7] found that SDAI and CDAI had concurrent validity and were highly predictive of a change in therapy.…”
Section: Discussionmentioning
confidence: 99%
“…7 NellDuxneuner et al 18 investigated the suitability of disease activity indices in patients with PsA and identified three major headings which contained five different components: (i) patient-related data (PaGA and patient pain assessment), (ii) jointrelated data (the number of tender and swollen joints), and (iii) acute phase reactants (CRP levels showed disease activity the best). These five components are reflected more thoroughly by the DAREA.…”
Section: Discussionmentioning
confidence: 99%
“…The Disease Activity Score including 28 joints (DAS28), 4 the Disease Activity Score for Reactive Arthritis (DAREA), 7 and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) 8 indices were used to assess the disease activity of the patients, and the Health Assessment Questionnaire (HAQ) 9 was applied for functional assessment. The results of the visual analog scale for pain (VAS-pain) (0-100 mm), patient global assessment (PaGA) and physician global assessment (PhGA) were also recorded.…”
mentioning
confidence: 99%